Cracks in the dike ; Spotlight: macho dancer ; Pinoy Internet Yehey! [videorecording] - Lazaro, Cheche (The Probe team, 1995)
Looks at the problems in Mt. Pinatubo devastated areas after its eruption; Pinoy call boys and male prostitutes; and discusses a Filipino information base, the Portal which can help the Filipino keep abreast with the times.